(untitled) (Journal of Economic Research & Business Administration, 2015)
It is shown value and a restructuring role in practice of corporate governance. Dynamics of development and feature of the Kazakhstan practice of corporate governance in coordination with branch structure and problems of the Kazakhstan economy is considered. Specifics of carrying out transactions of merges (absorption) as main mechanism of strategic restructuring of the Kazakhstan companies is revealed. It is shown that though restructuring with use of transactions of merges (absorption) already turned in Kazakhstan into the independent direction a razviktiya and increases of efficiency of business, however the equal coordinated transactions typical for the West between the enterprises on the basis of an exchange of actions thus didn’t gain distribution. The analysis of practice of raiding in the conditions of Kazakhstan is carried out. It is shown that raiding became a special type of business in which as goods the property right to the company is considered. Unlike the West countries in Kazakhstan raiding is understood only as unfriendly capture and merger of the enterprises with use of corruption schemes and other violations of laws. Characteristics are established and the main problems rising before the Kazakhstan companies at transactions of merge (absorption) are revealed. On their basis recommendations to the Kazakhstan companies developing strategy of restructuring with use of the transaction of merge (absorption) are formulated.